On majorants in the hardy-littlewood theorem for higher derivatives - Gorbaichuk, V. I.; Piddubnyi, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We establish conditions for majorants under which the classical Hardy-Littlewood theorem for the class of functions analytic in a disk is true in terms of derivatives of arbitrary fixed order.